Design and Evaluation of 223Ra-Labeled and Anti-PSMA Targeted NaA Nanozeolites for Prostate Cancer Therapy—Part II. Toxicity, Pharmacokinetics and Biodistribution - Lankoff, Anna; Czerwińska, Malwina; Walczak, Rafał; Karczmarczyk, Urszula; Tomczyk, Kamil; Brzóska, Kamil; Fracasso, Giulio; Garnuszek, Piotr; Mikołajczak, Renata; Kruszewski, Marcin (International journal of molecular sciences, 2021)
Metastatic castration-resistant prostate cancer (mCRPC) is a progressive and incurable disease with poor prognosis for patients. Despite introduction of novel therapies, the mortality rate remains high. An attractive alternative for extension of the life of mCRPC patients is PSMA-based targeted radioimmunotherapy. In this paper, we extended our in vitro study of 223Ra-labeled and PSMA-targeted NaA nanozeolites [223RaA-silane-PEG-D2B] by undertaking comprehensive preclinical in vitro and in vivo research. The toxicity of the new compound was evaluated in LNCaP C4-2, DU-145, RWPE-1 and HPrEC prostate cells and in BALB/c mice. The tissue distribution of 133Ba- and 223Ra-labeled conjugates was studied at different time points after injection in BALB/c and LNCaP C4-2 tumor-bearing BALB/c Nude mice. No obvious symptoms of antibody-free and antibody-functionalized nanocarriers cytotoxicity and immunotoxicity was found, while exposure to 223Ra-labeled conjugates resulted in bone marrow fibrosis, decreased the number of WBC and platelets and elevated serum concentrations of ALT and AST enzymes. Biodistribution studies revealed high accumulation of 223Ra-labeled conjugates in the liver, lungs, spleen and bone tissue. Nontargeted and PSMA-targeted radioconjugates exhibited a similar, marginal uptake in tumour lesions. In conclusion, despite the fact that NaA nanozeolites are safe carriers, the intravenous administration of NaA nanozeolite-based radioconjugates is dubious due to its high accumulation in the lungs, liver, spleen and bones.